Genuine Security for Whom?: Militourism and Violence Against the Feminine in Hawaiʻi and Asia and the Pacific - Nik Cristobal; Sam Ikehara; ʻIhilani Lasconia; Hina Kaʻōpua-Canonigo (Journal Committed to Social Change on Race and Ethnicity, 2024)
Assaults on ʻāina (land; that which feeds) are assaults on wāhine (women). Violence toward wāhine ʻōiwi (Native Hawaiian women/feminine people) and the ʻāina is discussed through the context of the Missing and Murdered Native Hawaiian Women, Girls, Māhū (MMNHWGM) movement and its relation to militourism. Militourism is used to draw parallels between the violence experienced by wāhine ʻōiwi in Hawaiʻi and women in the Philippines and across Asia and the Pacific. The concept of “genuine security” is addressed as a step toward sovereignty and reducing violence against wāhine and ʻāina. Reflective solutions to the violent impacts of militourism are offered through the frame of radical healing.